2013
DOI: 10.1016/j.matdes.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behaviour of AA6082-T6 MIG welded butt joints improved by friction stir processing

Abstract: Friction Stir Processing (FSP) was based on the principles of Friction Stir Welding (FSW), a solid-state joining process originally developed for aluminium alloys. It is an emerging metalworking technique which can provide localized modification and control of microstructures in near-surface layers of processed metallic components. In this research, FSP appears as an alternative to traditional methods for fatigue strength improvement of weld joints, such as re-melting, hammering and blasting,. This technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Specimens for fatigue test are usually sectioned and loaded perpendicular to the joint centerline [21][22][23][24][25][27][28][29][30][31]. Zhang [32] studied the fatigue fracture surface for a 6005 aluminum alloy FSW joint by Philips X130 SEM.…”
Section: Fractographymentioning
confidence: 99%
“…Specimens for fatigue test are usually sectioned and loaded perpendicular to the joint centerline [21][22][23][24][25][27][28][29][30][31]. Zhang [32] studied the fatigue fracture surface for a 6005 aluminum alloy FSW joint by Philips X130 SEM.…”
Section: Fractographymentioning
confidence: 99%
“…For example, Costa et al [10] [11] [12] [13] reported that grain refinement and stress concentration reduction due to FSP at the weld toe increased fatigue strength of several aluminum alloy joints fabricated by metal inert gas welding.…”
Section: Introductionmentioning
confidence: 99%
“…As far as cyclic stresses are concerned, welding defects inherent to the GMAW process are prone to crack initiation, which significantly reduces the fatigue performance of welded assemblies as compared to the base material 9,13 . Specifically, da Silva et al 14 reported that fatigue cracks initiate at the weld toe (i.e., at the interface of the welding pass and the HAZ) due to the combined effects of higher porosity, lack of wetting, and change of geometry due to the filler material reinforcement, resulting in high stress concentration in the toe weld region 9,14 .…”
Section: Introductionmentioning
confidence: 99%